Isolation of pigmentation mutants of the green filamentous photosynthetic bacterium Chloroflexus aurantiacus. - Pierson, B K (1984)
Mutants deficient in the production of bacteriochlorophyll c (Bchl c) and one mutant lacking colored carotenoids were isolated from the filamentous gliding bacterium Chloroflexus aurantiacus. Mutagenesis was achieved by using UV radiation or N-methyl-N'-nitro-N-nitrosoguanidine. Several clones were isolated that were deficient in Bchl c synthesis. All reverted. One double mutant deficient both in Bchl c synthesis and in the synthesis of colored carotenoids under anaerobic conditions was isolated. Isolation of a revertant in Bchl c synthesis from this double mutant produced a mutant strain of Chloroflexus that grew photosynthetically under anaerobic conditions and lacked colored carotenoids. Analysis of pigment contents and growth rates of the mutants revealed a positive association between growth rate and content of Bchl c under light-limiting conditions.